Integrated Marketing Communication Strategy To Increase The Number Of Outcoming Visits At Royal Prima Hospital - Annisa Soraya; Sri Wahyuni Nasution; Ermi Girsang; Chrismis Novalinda Ginting (CV. Inara, 2022)
Competition in a healthy hospital business lies in how to maintain patient trust as consumers or how to grow trust in prospective patients as consumers so that they want to seek treatment at the hospital. Integrated Marketing Communication (IMC) has great potential in influencing business performance, to give hospitals a competitive advantage. This study aims to analyze making a strategy to create an Integrated Marketing Communication strategy in order to increase the number of outpatient visits at the Royal Prima Hospital. This type of research is a qualitative research. The location of this research was conducted at the Royal Prima Hospital. Research informants are 1 head of outpatient installation, 3 medical staff, 3 old patients, 3 new patients. Data were collected by FGD, questionnaire, observation. The results show that the advertising strategy as part of increasing the number of outpatient visits at the Royal Prima Hospital has been carried out by the marketing department both with print media and electronic media, the personal selling strategy as part of increasing the number of outpatient visits at the Royal Prima Hospital has not been implemented. optimally, the public relations strategy as part of increasing the number of outpatient visits at the Royal Prima Hospital has been implemented well, the direct marketing strategy as part of increasing the number of outpatient visits at the Royal Prima Hospital in writing is good but verbal delivery is not optimal , the word of mouth strategy as part of increasing the number of outpatient visits at the Royal Prima Hospital in writing has been good but the verbal implementation has not been carried out properly. The results of this study suggest that the hospital evaluates the